New polymer nanocomposites for environmental remediation - Hussain, Chaudhery Mustansar; Mishra, Ajay Kumar, 1965- (Elsevier, 2018)
New Polymer Nanocomposites for Environmental Remediation summarizes recent progress in the development of materials' properties, fabrication methods and their applications for treatment of contaminants, pollutant sensing and detection. This book presents current research into how polymer nanocomposites can be used in environmental remediation, detailing major environmental issues, and key materials properties and existing polymers or nanomaterials that can solve these issues. The book covers the fundamental molecular structure of polymers used in environmental applications, the toxicology, economy and life-cycle analysis of polymer nanocomposites, and an analysis of potential future applications of these materials. Recent research and development in polymer nanocomposites has inspired the progress and use of novel and cost-effective environmental applications. Presents critical, actionable guidelines to the structure and property design of nanocomposites in environmental remediationFocuses on taking technology out of the lab and into the real world Summarizes the latest developments in polymer nanocomposites and their applications in catalytic degradation, adsorptive removal and detection of contaminants in the environment Enables researchers to stay ahead of the curve, with a full discussion of regulatory issues and potential new applications and materials in this area.